A Note on The Bell Jar (1963). (December 2013) - Behrens, Susan J
Abstract : Sylvia Plath's novel The Bell Jar, which first appeared in print fifty years ago, is a thinly veiled depiction of a particular time in the author's life, the summer of 1953. The protagonist and stand-in for Plath, Esther Greenwood, comes of age on the cusp of societal changes in the role of women in the US. Naming plays a central role in the development of Esther, a more pivotal one than has previously been recognized. Throughout the novel, Esther's journey toward mental breakdown and inability to find her true identity is paralleled by a failed struggle to accurately name herself.